CAD/CAE-метод вирішення гідродинамічної задачі при розробці потужних електронних приладів - Trofimov, V. E.; Pavlov, A. L.; Mamykin, Y. G. (PE "Politekhperiodika", Book and Journal Publishers, 2018)
The article presents examples of the solution of the hydrodynamic problem that arises in the development of powerful electronic devices requiring liquid cooling using the CAD/CAE modeling method. The authors consider poorly documented or undocumented features of such solution based on the use of free software packages — SALOME, OpenFOAM and ParaView for the CAELinux operating system platform.